JALAN tari pak Sal : penerima penghargaan seni Sasminta Mardawa 2016 / editor, Michael H. B. Raditya, Anastasia Melati - Michael H. B. Raditya; Anastasia Melati (Lintang Pustaka Utama, 2016)
x, 161 hlm. : ilus. ; 21 cm.